Identification Of Risk Events And Risk Agents In Goods Hoarding At The Port Using Fishbone Diagram - Maharani, Aditya; Rabbani, Latof Syeikhur (UNIPA PRESS, 2020)
X is a loading and unloading company (Perusahaan BongkarMuat/ PBM) which operates in the Port of Tanjung Perak, Surabaya. In 2018, the PBM experienced a hoarding of 65,698 tons of wirerod so the company had to issue a hoarding rate of Rp. 147,820,500. The fishbone diagram method is used to look for risk events and risk agents. From three main problems of goods hoarding, it is obtained the results of identification of risk events and risk agents, there are 17 risk events and 30 risk agents identified as triggers for the hoarding of goods at the port.